STUDY OF THE COMFORT LEVEL OF GREEN OPEN SPACE IN GEDONG TATAAN SUB-DISTRICT - Nia, Kurnia Albarkati; Christine Wulandari; Hari Kaskoyo; Samsul Bakri; Indra Gumay Febryano (Forestry Study Program University Of Mataram, 2025)
The conversion of land in urban areas, especially Green Open Space (GOS), into development land causes green land to decrease, coupled with the increasing volume of vehicles. The rapid activity of manufacturing plants and excessive energy consumption are contributing factors to the increase in CO2 in the air, and the quantity and quality of O2 is declining. Green Open Space or city park is an open space that has ecological benefits, the space is filled by trees that form vegetation, socio-cultural benefits as a forum for interaction between visitors, architectural and aesthetic benefits for the beauty of the city that can provide benefits in the form of recreational and tourist spaces for the community. The existence of RTH will improve air quality and comfort in densely populated areas. The method used is to calculate the Temperature Humidity Index (THI). The research aims to analyze the temperature and humidity that affect the comfort level of GOS in Gedong Tataan. Data is taken in October 2023. The results showed that the highest temperature was found in Gedong Tataan Park, which was 34.4 oC, and the lowest temperature was found in Jejama Sidototo Park, which was 25.8 oC. The difference in temperature and air humidity in the two RTHs in Gedong Tataan District is caused by differences in the composition of vegetation types. The diversity of vegetation types can reduce air temperature and increase humidity to provide comfort in both GOSs.